Political Anarchism and Raz’s Theory of Authority - Leipold, B (Springer Verlag, 2016)
This article argues that using Joseph Raz’s service conception of authority to reject philosophical anarchism can be affected by political anarchism. Whereas philosophical anarchism only denies the authority of the state, political anarchism claims that anarchism is a better alternative to the state. Raz’s theory holds that an institution has authority if it enables people to better conform with reason. I argue that there are cases where anarchism is an existing alternative to the state and better fulfils this condition. Consequently, in these cases, anarchist groups and societies and not the state have legitimate authority. When anarchism is not an existing alternative to the state, the state will, under Raz’s theory, have some legitimate authority, but that authority will be limited because anarchism remains a better possible alternative to the state. To support the political anarchist claim I discuss the anarchist collectives during the Spanish civil war, which I argue are an example of anarchism as an existing alternative to the state that better fulfils Raz’s service conception and also provide suggestive evidence that anarchism is in general a better possible alternative. I also discuss the relationship between political anarchism and authority and I argue that despite some tension they are not irreconcilable. I conclude that the interesting anarchist challenge for political theorists is political not philosophical.